Neuroendocrine carcinoma of cervix and review literature. (April 2023) - Verma, Saransh; Dubey, Harshita; Gupta, Swati; Ranjan, Amar; Goel, Harsh; Sharma, Anil
Abstract: Introduction: Neuroendocrine carcinoma of the cervix (NECC) is a rare variant of cervical cancer with poor prognosis and high mortality. Recurrence is seen with multi-organ metastasis including liver. Case presentation: A 65 year old female presented with vaginal bleeding for the past one year. Cervical cancer screening and biopsy demonstrated poorly differentiated squamous carcinoma. Immunohistochemistry showed positive expression of chromogranin, synaptophysin, pancytokeratin, TTP1, and CEA and negative expression of p40 and estrogen receptors. An adenocarcinoma with neuroendocrine tumor was suggested. Hysterectomy with bilateral salpingo-oophrectomy was performed. This was followed by carboplatin and etoposide therapy to have clinical remission for a year. Then recurrence was observed to start same drugs again resulting in to partial improvement. It was followed by radiotherapy. The patient succumbed to death approximately after three months. Conclusion: A metastatic lesion in liver may be a case of Neuroendocrine tumor of cervix, a rare condition that can be easily missed on histopathological examination. More studies are required to establish a standard therapeutic protocol. Highlights: Neuroendocrine tumor of cervix is a rare condition that can be easily missed on histopathological examination. Due to aggressive nature of cervical neuroendocrine tumor, patients must be kept under careful observation. Metastasis in such cases, particularly to the liver, lungs, and rib cage, must be kept in mind. Pregnancy associated neuroendocrine tumor needs a personalized therapeutic approach. More case studies are required to establish a standard therapeutic protocol.